Forest dynamics of a sub-xerophilous vegetation formation in central Peru-Chanchamayo valley, Peru [Dinâmica florestal de uma formação vegetais sub-xerófila no valor de Chanchamayo, departamento Junin, Peru] - Palacios-Ramos S. (2018)
WethankRobin Fernández,Aniceto Daza and José LuisMarceloPeñafromtheUniversidadNacionalAgraria LaMolina Herbarium(MOL:Woody plants collection), for their contributions to taxonomic identification. To IRD-Selva Central - UNALM for help in establishing andcensusofthepermanentplot.Wethankthereviewers for their contribution to improve the manuscript. This study was supported by Cienciactiva, CONCYTEC.